Measurement uncertainty revealed: The impacts of Certified Reference Material (CRM) on cannabinoid concentrations in the cannabis testing industry - Stephen Goldman (Talanta Open)
Potency testing in the cannabis industry is one of the most important tests currently performed. Due to its financial importance, there exists a lot of pressure to achieve potency values that are as high as possible, while staying within the realm of what is morally correct to perform. This paper explains how potency testing is achieved and how differences due to lack of standardization may exist. The paper then explores measurement error, or uncertainty, and suggests reference material may be the largest contributor to this uncertainty in the market today.